The corporate strategy of increasing the visibility of websites by implementing digital marketing - Bytyçi, Shaip; Kelmendi, Jeton; Shala, Venet; Myftaraj, Ervin; Hasrama, Erjonilda (Edelweiss Applied Science and Technology, 2024)
Increasing the visibility of websites by implementing digital marketing is deeply affecting every sphere of life, especially in all economic activities. Websites with more community-focused pages—such as blogs, forums, and connections to other social media sites—are seen more frequently Pant et al. (2017). By utilizing an e-commerce website for digital marketing, business owners may more effectively promote their items and quickly see sales figures Supriyatin, W., & Wisesha, K. (2022).The main aim of the study is to analyze the importance of the increasing the visibility of websites by implementing digital marketing in case of business. The mthodology used consist on qualitative method. Primary data were used to test the hypotheses in the study, while the online questionnaire was used as the research tool for data collection. The questionnaire was prepared in "google forms" and covered a six-month time period for data collection. Respondents were randomly selected after the questionnaire was administered online to a random sample of 150 participants. The study finds that the impact on increasing the visibility of websites in the selection of a search engine by implementing digital marketing is more than just a search. Internet searches in the visibility of specific pages, are a key element in the company's relationship with consumers, which represent perceptions and feelings of consumers about a product or service in which it is related to their performance, which represent everything that means for the product or service to consumers.